Anaerobic Degradation of 2-Methylnaphthalene by a Sulfate-Reducing Enrichment Culture - Annweiler, Eva (American Society for Microbiology, 2000)
Anaerobic degradation of 2-methylnaphthalene was investigated with a sulfate-reducing enrichment culture. Metabolite analyses revealed two groups of degradation products. The first group comprised two succinic acid adducts which were identified as naphthyl-2-methyl-succinic acid and naphthyl-2-methylene-succinic acid by comparison with chemically synthesized reference compounds. Naphthyl-2-methyl-succinic acid accumulated to 0.5 μM in culture supernatants. Production of naphthyl-2-methyl-succinic acid was analyzed in enzyme assays with dense cell suspensions. The conversion of 2-methylnaphthalene to naphthyl-2-methyl-succinic acid was detected at a specific activity of 0.020 ± 0.003 nmol min(−1) mg of protein(−1) only in the presence of cells and fumarate. We conclude that under anaerobic conditions 2-methylnaphthalene is activated by fumarate addition to the methyl group, as is the case in anaerobic toluene degradation. The second group of metabolites comprised 2-naphthoic acid and reduced 2-naphthoic acid derivatives, including 5,6,7,8-tetrahydro-2-naphthoic acid, octahydro-2-naphthoic acid, and decahydro-2-naphthoic acid. These compounds were also identified in an earlier study as products of anaerobic naphthalene degradation with the same enrichment culture. A pathway for anaerobic degradation of 2-methylnaphthalene analogous to that for anaerobic toluene degradation is proposed.